Transcriptome Profiling Reveals a Petunia Transcription Factor, PhCOL4, Contributing to Antiviral RNA Silencing - Xu, Yingru; Ji, Xiaotong; Xu, Zhuangzhuang; Yuan, Yanping; Chen, Xiling; Kong, Derong; Zhang, Yanlong; Sun, Daoyang (Frontiers in Plant Science, 2022)
RNA silencing is a common antiviral mechanism in eukaryotic organisms. However, the transcriptional regulatory mechanism that controls the RNA silencing process remains elusive. Here, we performed high-depth transcriptome analysis on petunia (Petunia hybrida) leaves infected with tobacco rattle virus (TRV) strain PPK20. A total of 7,402 differentially expressed genes (DEGs) were identified. Of them, some RNA silencing-related transcripts, such as RNA-dependent RNA polymerases (RDRs), Dicer-like RNase III enzymes (DCLs), and Argonautes (AGOs), were induced by viral attack. Furthermore, we performed TRV-based virus-induced gene silencing (VIGS) assay on 39 DEGs encoding putative transcription factors (TFs), using green fluorescent protein (GFP) and phytoene desaturase (PhPDS) as reporters. Results showed that the down-regulation of PhbHLH41, PhbHLH93, PhZPT4-3, PhCOL4, PhHSF-B3A, PhNAC90, and PhWRKY75 led to enhanced TRV accumulation and inhibited PhPDS-silenced photobleaching phenotype. In contrast, silencing of PhERF22 repressed virus accumulation and promoted photobleaching development. Thus, these TFs were identified as potential positive and negative regulators of antiviral RNA silencing, respectively. One positive regulator PhCOL4, belonging to the B-box zinc finger family, was selected for further functional characterization. Silencing and transient overexpression of PhCOL4 resulted in decreased and increased expression of several RNA silencing-related genes. DNA affinity purification sequencing analysis revealed that PhCOL4 targeted PhRDR6 and PhAGO4. Dual luciferase and yeast one-hybrid assays determined the binding of PhCOL4 to the PhRDR6 and PhAGO4 promoters. Our findings suggest that TRV-GFP-PhPDS-based VIGS could be helpful to identify transcriptional regulators of antiviral RNA silencing.